Liberalism, Multiculturalism and Toleration
XI, 209 p.
Keywords: The publication of Salman Rushdie's novel The Satanic Verses has provoked fierce debate about the scope of toleration in a modern multicultural society. This volume explores the philosophical issues arising from this debate from a variety of points of view. It includes both general discussions of the relationship between liberalism, toleration and multiculturalism, and several essays devoted specifically to the implications of the Rushdie affair for liberal political theory and its practical commitment to toleration.